Expression of Curli by Escherichia coli O157:H7 Strains Isolated from Patients during Outbreaks Is Different from Similar Strains Isolated from Leafy Green Production Environments - Ravva, Subbarao V.; Sarreal, Chester Z.; Cooley, Michael B. (Frontiers in Cellular and Infection Microbiology, 2016)
We previously reported that the strains of Escherichia coli O157:H7 (EcO157) that survived longer in austere soil environment lacked expression of curli, a fitness trait linked with intestinal colonization. In addition, the proportion of curli-positive variants of EcO157 decreased with repeated soil exposure. Here we evaluated 84 and 176 clinical strains from outbreaks and sporadic infections in the US, plus 211 animal fecal and environmental strains for curli expression. These shiga-toxigenic strains were from 328 different genotypes, as characterized by multi-locus variable-number tandem-repeat analysis (MLVA). More than half of the fecal strains (human and animal) and a significant proportion of environmental isolates (82%) were found to lack curli expression. EcO157 strains from several outbreaks linked with the consumption of contaminated apple juice, produce, hamburgers, steak and beef were also found to lack curli expression. Phylogenetic analysis of fecal strains indicates curli expression is distributed throughout the population. However, a significant proportion of animal fecal isolates (84%) gave no curli expression compared to human fecal isolates (58%). In addition, analysis of environmental isolates indicated nearly exclusive clustering of curli expression to a single branch of the minimal spanning tree. This indicates that curli expression depends primarily upon the type of environmental exposure and the isolation source, although genotypic differences also contribute to clonal variation in curli. Furthermore, curli-deficient phenotype appears to be a selective trait for survival of EcO157 in agricultural environments.